2000
DOI: 10.1093/oxfordjournals.jbchem.a022753
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Virus-Induced Homomeric and Heteromeric Protein Associations between IRF-3 and Coactivator CBP/p300

Abstract: Cellular genes including the type I interferon genes are activated in response to viral infection. We previously reported that IRF-3 (interferon regulatory factor 3) is specifically phosphorylated on serine residues and directly transmits a virus-induced signal from the cytoplasm to the nucleus, and then participates in the primary phase of gene induction. In this study, we analyzed the molecular mechanism of IRF-3 activation further. The formation of a stable homomeric complex of IRF-3 between the specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
87
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 25 publications
3
87
0
Order By: Relevance
“…In cells transfected with IRF7 alone or IRF3 alone, we sometimes detected two specific bands in EMSA, one of which ran faster than VAF⅐DNA complex (data not shown), suggesting that IRF7 or IRF3 homodimers may be involved in IRF7 regulation. Also, previous reports have shown that IRF3 or IRF7 homodimers are involved in the activation of their target genes (36,54). IRF7 homodimers form in the absence of phosphorylation (55).…”
Section: Discussionmentioning
confidence: 92%
“…In cells transfected with IRF7 alone or IRF3 alone, we sometimes detected two specific bands in EMSA, one of which ran faster than VAF⅐DNA complex (data not shown), suggesting that IRF7 or IRF3 homodimers may be involved in IRF7 regulation. Also, previous reports have shown that IRF3 or IRF7 homodimers are involved in the activation of their target genes (36,54). IRF7 homodimers form in the absence of phosphorylation (55).…”
Section: Discussionmentioning
confidence: 92%
“…According to their model, the inhibition is reversed by the phosphorylation of the 5ST site, which confers negative charges to the inhibitory domain, resulting in a dramatic conformational change (12 However, the model is inconsistent with several observations. First, the deletion mutant IRF-3 (1-394), originally described as constitutively active (12), was not active even after viral stimulation (13). The 5D mutant was active as reported when produced in human 293T cells (12); however, it was much less active in mouse L929 cells (13) and was produced as an inactive monomer in Escherichia coli.…”
mentioning
confidence: 92%
“…Recently, IKK-i (also known as IKK-⑀) and TBK-1 were shown to function as IRF-3 kinases (10,11). The phosphorylated IRF-3 undergoes homodimerization (12,13) and associates with coactivators CBP/ p300, and then a holocomplex of IRF-3 results (5,12). The holocomplex is conferred an ability to specifically recognize the target DNA sequence and accumulate in the nucleus (5,14,15).…”
mentioning
confidence: 99%
See 2 more Smart Citations